Functional assignment of technological accessories for woodworking - Tsapko, Yu; Bondarenko, O.; Tsapko, O.; Gorbachova, A.; Mazurchuk, S.; Zherebchuk, D (Ways to Improve Construction Efficiency, 2023)
Forming a heat and sound insulation board from wood using non-combustible binders can increase the fire protection of the material by forming a protective layer of coke. This will make it possible to develop a new type of fireproof roofing products for building structures. It is not always advisable to treat the surface of a heat and sound insulation board with fireproof coatings, since after prolonged thermal exposure, the combustion stage can be transferred to the interior of the material by smoldering. Therefore, the manufacture of fire-resistant heat- and sound-insulating wood materials, the study of fire protection and the impact of their components on this process is an unresolved component of ensuring the fire resistance of building structures. And, accordingly, they determine the need for such research. The paper presents the results of research into the process of protecting wood wool boards with binders based on fire-resistant coatings. Tests on model samples of a wooden board showed that the material based on wood wool and an inorganic binder is characterized by heat absorption and inhibition of oxidation in the gas and condensed phase and the formation of a thermally protective ceramic layer on the surface of the wood. Experimental studies have confirmed that a material based on wood wool and an inorganic binder at a ratio of 1:1 refers to combustible materials, since its smoldering was recorded during exposure to temperature. So, by thermal action for 90 s, the material ignited and the flame spread over the first three zones for 41 s. On the other hand, an increase in the amount of an inorganic-based binder and the use of an organic-mineral binder does not lead to a material fire. In this case, the maximum temperature of the flue gases was about 120 °C, and the flammability index was 0 due to the decomposition of fire retardants under the influence of temperature with the release of incombustible gases, which inhibit the oxidation of the material and significantly increase the formation of a heat-protective layer of coke on the surface of the material. This leads to inhibition of heat transfer of the high-temperature flame to the material. Due to this, it became possible to determine the conditions of fire resistance of the material by forming a barrier for thermal conductivity. The obtained results indicate the possibility of targeted regulation of high temperature transfer processes to organic material by using special binders for wood products.